2016
DOI: 10.1111/anae.13572
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity of a novel assessment tool for ultrasound‐guided axillary brachial plexus block

Abstract: The purpose of this study was to examine the construct validity and reliability of a novel metrics-based assessment tool, previously developed for ultrasound-guided axillary brachial plexus block. Five expert and eight novice anaesthetists performed a total of 18 ultrasound-guided axillary brachial plexus blocks on the same number of patients. A trained investigator video-taped procedures according to a pre-defined protocol. Two trained consultant anaesthetists independently scored the videos using the assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Our methods outlined an objective approach to providing feedback to improve skills performance of ultrasound‐guided axillary brachial plexus blockade. We used a metric‐based assessment tool that was previously generated using a detailed ‘task characterisation’, and has been proven to demonstrate construct validity and a high degree of reliability within the context of ultrasound‐guided axillary brachial plexus block . The high inter‐rater reliability (as assessed by agreement between the two video assessors) observed in this study is consistent with our previous findings, when the assessment tool was used to assess performance in clinical settings.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our methods outlined an objective approach to providing feedback to improve skills performance of ultrasound‐guided axillary brachial plexus blockade. We used a metric‐based assessment tool that was previously generated using a detailed ‘task characterisation’, and has been proven to demonstrate construct validity and a high degree of reliability within the context of ultrasound‐guided axillary brachial plexus block . The high inter‐rater reliability (as assessed by agreement between the two video assessors) observed in this study is consistent with our previous findings, when the assessment tool was used to assess performance in clinical settings.…”
Section: Discussionsupporting
confidence: 85%
“…For the metrics‐based feedback group, feedback was provided to each participant in this group using a list of metrics (steps and errors) extracted from a previously validated assessment tool (Table ). Participants practised each item of the checklist in sequence until it was satisfactorily performed, as assessed by the supervising consultant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study of UGRA performance, we have demonstrated that both the AC and the GRS may be used to differentiate between individuals who have performed fewer (30) and many (>100) nerve blocks in the preceding year; this finding is consistent with the findings of the recent study of Ahmed and colleagues. 12 However, neither assessment tool was sufficiently sensitive to identify the anaesthetists who had performed an intermediate number of nerve blocks (31e100) in the preceding year. This could represent a Type 2 error, rather than a lack of sensitivity in the assessment tools, although our sample size is in line with similar and recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…This has been investigated recently using a prospective observational design 22. Future studies are required to evaluate the effectiveness of new training programs based on these metrics.…”
Section: Discussionmentioning
confidence: 99%